Preparation of a Novel Nano-scale Lead (II) Zig-Zag Metal–Organic Coordination Polymer with Ultrasonic Assistance: Synthesis, Crystal Structure, Thermal Properties, and NBO Analysis of [Pb(μ-2-pinh)N3 H2O]n - Mirtamizdoust, Babak; Bieńko, Dariusz C.; Hanifehpour, Younes; Tiekink, Edward R. T. *; Yilmaz, Veysel T.; Talemi, Pejman; Joo, Sang Woo (Springer Verlag (Germany), 2016)
A novel nano-cauliflower-shaped lead(II) metal–organic coordination polymer, [Pb(μ-2-pinh)N3 H2O]n (1), was synthesized using an ultrasonic method. The nanostructure was characterized by scanning electron microscopy (SEM), X-ray powder diffraction, IR spectroscopy, elemental analysis, and thermal analysis. The compound was structurally characterized by single-crystal X-ray diffraction. The coordination compound takes the form of a zig-zag one-dimensional polymer in solid state. The coordination number of the lead(II) ions is six (PbN4O2) with three nitrogen atoms and one oxygen atom from two linker organic ligands, as well as one oxygen from coordinated water and one nitrogen atom from terminal coordinated azide anion. It has a stereo-chemically active lone electron pair, and the coordination sphere is hemidirected. The zig-zag 1D chains interact with neighbouring chains through weak interactions, creating a 3D supramolecular metal–organic framework. Lead oxide nanoparticles were obtained by thermolysis of the new nano coordination compound at 180 °C with oleic acid as a surfactant. The morphology and size were further studied using SEM. Natural bond orbital analyses demonstrate the electronic properties of the lead centre and other atoms.